The Ability of Prospective Elementary School Teachers in Developing Civics Learning Modules in Elementary Schools - Kasim, Indri Rahmawati; Kawuryan, Sekar Purbarini; Saptono, Bambang; Fathurrohman; Adiwardana, Muh Rifqienur; Herawati, Yuli (International Journal of Elementary Education, 2024)
The curriculum serves as the objective to guide education. Teaching modules are designs or instructional tools that are based on the curriculum and are used to meet established competency standards. It underscores the importance for educators to use teaching modules when developing lessons. The aims of this study is to analyze the ability of students enrolled in an elementary teacher education program to develop a Civics teaching module for elementary schools. This research is of a qualitative descriptive type, with data collection methods including observation, questionnaires, and documentation, employed in this qualitative study. The subjects in this study are 47 sixth-semester students from class 6E, comprising 7 male students and 40 female students from 12 groups selected based on their ability to develop teaching modules categorized as very good, good, fair, and less good. The research instrument uses an interval scale questionnaire of the Likert scale type. The results of PGSD students' ability in developing curriculum-based teaching modules were obtained after calculating each group's score based on the assessment rubric for each component. The overall percentage result is 80.70%, which falls into the "Good" category. Based on the research results, it can be concluded that the majority of students have good abilities in developing Civic Education teaching modules in elementary schools according to the indicators of the Free Curriculum teaching modules.